The transcription factor Dysfusion promotes fold and joint morphogenesis through regulation of Rho1. - Sergio Córdoba; Carlos Estella (PLoS Genetics, 2018)
The mechanisms that control tissue patterning and cell behavior are extensively studied separately, but much less is known about how these two processes are coordinated. Here we show that the Drosophila transcription factor Dysfusion (Dysf) directs leg epithelial folding and joint formation through the regulation of Rho1 activity. We found that Dysf-induced Rho1 activity promotes apical constriction specifically in folding epithelial cells. Here we show that downregulation of Rho1 or its downstream effectors cause defects in fold and joint formation. In addition, Rho1 and its effectors are sufficient to induce the formation of epithelial folds when misexpressed in a flat epithelium. Furthermore, as apoptotic cells can actively control tissue remodeling, we analyzed the role of cell death in the formation of tarsal folds and its relation to Rho1 activity. Surprisingly, we found no defects in this process when apoptosis is inhibited. Our results highlight the coordination between a patterning transcription factor and the cellular processes that cause the cell shape changes necessary to sculpt a flat epithelium into a three dimensional structure.